Pengaruh Nilai Tukar terhadap Return Saham dengan Profitabilitas sebagai Variabel Intervening - Puspita Lestari, Made Dewi Gita; Agung Suaryana, I Gusti Ngurah (E-Jurnal Akuntansi; Vol 30 No 5 (2020), 2020)
The research aims to examine the effect of exchange rates on stock returns through profitability. The study was conducted on mining companies listed on the Stock Exchange which numbered 49 companies. Samples were determined by a purposive sampling method totaling 7 companies that were studied for 3 years of observation using quarterly reports, so there are 84 observation datas. Data collection methods and data analysis techniques used are non-participant observation methods and path analysis. The results showed that the exchange rate had a significant negative effect on stock returns and profitability. Profitability has a significant positive effect on stock returns, and exchange rates have indirect influence on stock returns through profitability. Keywords: Stock Returns; Exchange Rates; Profitability.